ISLAMIC BOARDING SCHOOL UPDATES: Study of Management and Education System at Darularafah Raya Islamic Boarding School, Deli Serdang - Imam Rinaldi; faisal faisal; Novi Sriyanti (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This research aims to describe: 1) management dynamics of Pesantren Darularafah Greater, 2) dynamics of education system in Pesantren Darularafah Raya. This research uses a qualitative method. Data obtained through interviews, observation and documentation. The informant in this research is the founder of Pesantren Darularafah Raya as the general leader of Pesantren, Darularafah Raya principal / head of madrasah, ustadz / ustadzah, and some santri and dyah who can provide additional information to the required data. Data analysis is done through data reduction, data presentation and conclusion. The results showed that: 1) Management in Pesantren Darularafah Raya has been managed in a neat and professional manner, this is evidenced by the planning (planning), organizing (organizing), actuating, and control (controlling) is good, conducted Pesantren Darularafah Raya. 2) The educational system consists of educational objectives, educator and educational situation, curriculum, and facilities / infrastructure. Every year there is dynamics in the education system at Pesantren Darularafah, this is evidenced by the evaluation or evaluation of the performance of educators every year.